GENERAL MAGNETIC FIELD OF THE SUN AS A ST AR AS INDICA TOR OF MASSIVE STREAMS FLOWING ON THE SUN - Plachinda, S.; Baklanova, D.; Han, I.; Kim, K. M.; Reegen, P.; Valyavin, G.; Weiss, W. (Одеські астрономічні публікації, 2008)
The behaviour of the General Magnetic Field of the Sun as a Star (GMFSS) is characterized by the change of amplitude of oscillations with the eleven-year cycle of activity. In maximum of activity GMFSS reaches its maximal values, and in a minimum reaches minimal values. The values of active frequencies vary from cycle to cycle of sunspots activity. Each peak of GMFSS power spectrum is widened by the number of active frequencies. From observations of GMFSS the velocity of solar photosphere movements deviates from the speed of the differential rotation of the Sun more than 5 ms -1 mas it follows from gelioseismology. For 40 years of direct observations (two solar magnetic cycles) resulting magnetic field of GMFSS is non equal to zero. GMFSS demonstrates properties of a real large-scale field because there is a balance of positive and negative magnetic fluxes, i.e. the magnetic tubes are closed.